Metal- and Solvent-free Synthesis of Functionalized Dihydrooxazolo[3,2-a]indoles by One-Pot Tandem Assembly of 3H-Indoles and Propargylic Alcohols - Oparina, Ludmila A.; Kolyvanov, Nikita A.; Ushakov, Igor A.; Mal’kina, Anastasiya G.; Vashchenko, Alexander V.; Trofimov, Boris A. (Synthesis, 2019)
The reaction of 3H-indoles with tertiary propargylic alcohols to give functionalized dihydrooxazolo[3,2-a]indoles in good to excellent yields has been developed. This metal- and solvent-free, one-pot tandem assembly proceeds under mild conditions (22–60 °C) and is regio- and stereoselective: either the Z- or E-isomers (relative to the double bond) are alternatively formed depending on other functionalized substituents on the propargylic alcohols.
Keywords: 3H-indole; 1H-benzo[e]indole; propargylic alcohols; annulation; dihydrooxazolo[3,2-a]indoles